2010
DOI: 10.1002/jssc.201000293
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high‐selective HPLC packing materials based on alternating copolymer‐grafted silica

Abstract: Three alternating copolymer-grafted silica stationary phases for use in high-selective RP-HPLC were prepared from two vinyl monomers selected from styrene, N-methylmaleimide, N-octadecylmaleimide, and octadecyl acrylate; they were characterized by elemental analyses, thermogravimetric analysis, diffuse reflectance infrared Fourier transform spectroscopy, and (13)C cross-polarization magic-angle spinning NMR spectroscopy. Aspects of molecular-shape selectivity were evaluated for three different columns using St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Recently, we found that N-substituted maleimide-based alternating copolymer-grafted silica phase showed very good molecular-shape selectivity as well as the enhancement of separation selectivity [10,22,23]. We already proved that stabilization of polymer main chain and consequently orientation of weak interaction sites is possible by alternating copolymerization, which helps to increase selectivity [24].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we found that N-substituted maleimide-based alternating copolymer-grafted silica phase showed very good molecular-shape selectivity as well as the enhancement of separation selectivity [10,22,23]. We already proved that stabilization of polymer main chain and consequently orientation of weak interaction sites is possible by alternating copolymerization, which helps to increase selectivity [24].…”
Section: Introductionmentioning
confidence: 98%
“…A number of efforts have been done toward developing an understanding of shape selective interactions between the stationary phase and the analyte and have already been reported for alkyl phases. ,,, However, a systematic theory describing the molecular interaction between analytes and bonded phase ligands has not been firmly established because of difficulties encountered in the surface characterization of these C 18 stationary phases. However, in the past 20 years, various newly synthesized bonded phases have been introduced as stationary phases, which include synthetic and bonding chemistries. Because these new stationary phases could be synthesized according to the design of the bonded phase ligands, the systematic characterization of stationary phases has become increasingly important for the development of more powerful stationary phases with desirable separation performance for specific uses.…”
mentioning
confidence: 99%